Role of different vascular approaches on transcatheter aortic valve implantation outcome: a single-center study. Issue 4 (April 2015) - Adamo, Marianna; Fiorina, Claudia; Curello, Salvatore; Maffeo, Diego; Chizzola, Giuliano; Di Matteo, Gerardo; Mastropierro, Rosa; Nardi, Matilde; Cervi, Edoardo; De Cicco, Giuseppe; Chiari, Ermanna; Curnis, Antonio; et al.
Abstract : Objective: To compare different vascular approaches on clinical outcome of patients undergoing transcatheter aortic valve implantation (TAVI) with self-expandable bioprosthesis. Methods: We included all the patients undergoing CoreValve implantation at our institute between September 2007 and March 2014. They were divided into four groups based on the vascular approach: percutaneous transfemoral (pTF), cut-down transfemoral (cTF), transaxillary (TAx) and transaortic (TAo). Clinical outcomes were evaluated according to Valve Academic Research Consortium-2 recommendations. Results: Out of 322 consecutive patients, 170 (53%) underwent pTF, 76 (23%) cTF, 32 (10%) TAx and 44 (14%) TAo approach. Although the TAx and TAo patients had a higher risk profile, they had a similar outcome compared with the pTF and cTF groups; in particular, there were no differences regarding cardiovascular and all-cause mortality at 30 days, 1 and 2 years, as well as stroke, myocardial infarction, bleeding, major vascular complications, permanent pacemaker implantation and acute kidney injury rates. The observed device success rate was higher in the TAo than in the other approaches (88.6 versus 65.9, 68.7 and 76.3% in the pTF, cTF and TAx groups, respectively; P = 0.019). No differences occurred regarding 30-day early safety and 1-year clinical efficacy across the four groups. Fluoroscopy time, amount of contrast medium used and minor vascular complications were significantly higher in pTF patients, as well as in-hospital stay in the TAo group. Atrial fibrillation and prosthetic valve regurgitation, but not the vascular approach, were independent predictors of all-cause mortality. Conclusion: A more invasive vascular approach, for CoreValve implantation, even in higher risk patients, does not affect early-term, mid-term and long-term outcomes.